Aging and Municipality Administrations: Istanbul Kad?koy Case - Kurtkapan, Hamza (European Journal of Multidisciplinary Studies, 2017)
The aim of this article is to form a sociological perspective for new applications and to evaluate the local authority applications by observing the effects of urbanization on ‘aging’ and ‘being old’. There is a swift transformation process in Turkey’s social life. Family structure is also changing along with the social transition occurring in the urbanization process. Elders are the main actors that this transition effects and their position has been changed in society. With the social change, something about elders has become problematic with family bands. With urbanization, elders have been faced with ‘loneliness’, ‘cost of living’, and ‘service care’ problems. To overcome these cases, special social supports and raising local authority’s consciousness of responsibility is needed. Although aging in Turkey is not as vital a ‘problem’ as in developed societies, it is obvious that there is an upward movement. As a result of increased living standards and development in health areas, average human lifespan and life expectancy has increased. Although Turkey has a young population percentage-wise, the actual number of elder people is quite high. The increment in elderly population in Turkey and reasons like the change of family structure, which make elder service important, are influential factors determining the subject of this thesis. Within this framework, supporting home care service is a goal. Towards this aim, the social problems that elders may face in urban areas and solving applications for these problems will be evaluated from a sociological perspective. Within this research, it is aimed to understand urban elders’ life from a new perspective. Another way of understanding social processes is to observe the process and to conduct interviews with the related actors. Questions in our study will be divided into “factual questions” and “comparative questions”. In this study, mainly two resources will be used, primary sources, defined as oldies who are living in urban areas and encounter the opportunities and difficulties of this city, their families and health workers who have a direct interaction with oldies, the opinions of people (largely city officials) and as minor sources, firstly sociology and the literature of books, theses, articles, reports etc. which are about soc?al science. The methodological tendency of this study will be in qualitative form because of the general features of oldies that are its object. The semi-structured form will be applied to measure the assessments of people who are in contact with oldies and also their personal life, economic status, lifestyle, family, kinship, neighbor relations and their expectations of life. Beyond generalizing about oldies in this study, to make a case determination will be tried as a feature of the qualitative study method. We aim to carry out the study in the framework of one of the qualitative study types, using the data collection techniques of literature survey, questionnaire, and meeting (structured, not-structured) will be used for our study with different dimensions of observation techniques.